2016
DOI: 10.1590/1679-78252725
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Stay Cables of a Bridge Under Simulated Spatially Correlated Turbulent Wind

Abstract: The main objective of this work is to carry out a parametric study of stay cables of a bridge under simulated spatially correlated buffeting forces. This vibration mechanism is simulated with an Autoregressive and Moving Average (ARMA) model, and applied to mathematical models of the stay cables of the tallest cablestayed bridge in Mexico. The use of auxiliary damping devices to mitigate vibration is evaluated. The analysis results showed that the use of a more realistic model to represent and characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Baluarte Bridge is a cable-stayed bridge with a mid-span length of 520 m in Mexico. The study on the buffeting response of this bridge showed that the calculation results using the frequency-domain analysis are less than 30% of the full aeroelastic model wind tunnel test results, while the results of time-domain analysis are close to the experimental results [17][18][19]. Nowadays, the time-domain analysis method has been widely used with the improvement of numerical calculation ability [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 88%
“…Baluarte Bridge is a cable-stayed bridge with a mid-span length of 520 m in Mexico. The study on the buffeting response of this bridge showed that the calculation results using the frequency-domain analysis are less than 30% of the full aeroelastic model wind tunnel test results, while the results of time-domain analysis are close to the experimental results [17][18][19]. Nowadays, the time-domain analysis method has been widely used with the improvement of numerical calculation ability [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 88%